If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + -7 = 4p + 3 Reorder the terms: -7 + 5p = 4p + 3 Reorder the terms: -7 + 5p = 3 + 4p Solving -7 + 5p = 3 + 4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4p' to each side of the equation. -7 + 5p + -4p = 3 + 4p + -4p Combine like terms: 5p + -4p = 1p -7 + 1p = 3 + 4p + -4p Combine like terms: 4p + -4p = 0 -7 + 1p = 3 + 0 -7 + 1p = 3 Add '7' to each side of the equation. -7 + 7 + 1p = 3 + 7 Combine like terms: -7 + 7 = 0 0 + 1p = 3 + 7 1p = 3 + 7 Combine like terms: 3 + 7 = 10 1p = 10 Divide each side by '1'. p = 10 Simplifying p = 10
| 4m-5=6m+d | | (2x+1)+y=56 | | 16-3p=-21 | | 110+(3x-20)=180 | | 4x+12+34=180 | | 9x-8y=16 | | x^3-5x^2+2x+10=0 | | x^3-5x+2x^2+10=0 | | x^3-15=39 | | 12+x-x^2= | | 20-x-x^2= | | 14-5x-x^2= | | 9(x-4)+2(1+4x)=0 | | 12+4x-x^2= | | 2a-10=-8 | | 5-4x-x^2= | | -5(-3-x)-12=3(1+11x) | | 4x+7=6x-2 | | -11+8x=5x+7 | | 2x-45=15 | | -4x+-3(x-5)=8x | | 8+2x-x^2= | | 8x-9=8(x-1)+1 | | 2x-21x+20=0 | | 5+6d=10+1d | | 64.00+x=67.68 | | 10(x+7)=10(x+11) | | 10x-7=10x-7 | | (3x+7)+(3x-5)=0 | | 2(x-3.00)=10.80 | | 10x+y=53 | | 10x+6=12x-5 |